(untitled) (Academicia Globe: Inderscience Research, 2022)
It is the oldest branch of agricultural production. The role of agriculture in the world economy has been growing rapidly in recent years, indicating that the role of agriculture in the world economy is growing. The main task of agriculture is to meet the needs of the population for food and industry for raw materials in order to ensure the sustainability of agricultural production and increase economic efficiency.